Postcolonial intellectuals in Europe critics, artists, movements, and their publics - Ponzanesi, Sandra 1967-; Habed, Adriano José (Frontiers of the political: doing international politics, 2020)
"Offers overview of postcolonial intellectuals in Europe from the first half of the nineteenth century to present day"...